2012
DOI: 10.1007/s00280-012-2045-1
|View full text |Cite
|
Sign up to set email alerts
|

A phase I dose-escalation trial of 2-deoxy-d-glucose alone or combined with docetaxel in patients with advanced solid tumors

Abstract: The recommended dose of 2DG in combination with weekly docetaxel is 63 mg/kg/day with tolerable adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
360
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(372 citation statements)
references
References 24 publications
7
360
1
4
Order By: Relevance
“…2-DG has been recently tested in phase I trials (49,50). Pharmacokinetics studies have shown that mmol/L concentrations of 2-DG were hardly achievable at the maximal-tolerated doses and thus, although we do not observed significant toxicity in mice, achieving antitumoral concentrations in human could be challenging.…”
Section: Discussionmentioning
confidence: 67%
“…2-DG has been recently tested in phase I trials (49,50). Pharmacokinetics studies have shown that mmol/L concentrations of 2-DG were hardly achievable at the maximal-tolerated doses and thus, although we do not observed significant toxicity in mice, achieving antitumoral concentrations in human could be challenging.…”
Section: Discussionmentioning
confidence: 67%
“…2-DG is an analog of glucose, which is phosphorylated by HKs but not metabolized further, thus it is used as a HK inhibitor by many studies and in clinical trials for cancer therapy. [161][162][163] We observed that a low concentration of 2-DG (500 μM compared Bax/Bak, t-Bid mPTP ROS emission Figure 3 MitoHK-II regulation and mitochondrial protection…”
Section: Hk-ii-mediated Regulation Of Mtorc1 and Autophagymentioning
confidence: 87%
“…This molecule is well tolerated 25,26 and might offer important advantages over molecules such as Tolvaptan, which has action that is limited to cysts originating from specific segments of the nephron (distal tubules and collecting ducts). 10 Furthermore, we speculate that 2DG might be active in cysts originating in other organs, such as the bile ducts in the liver or pancreatic cysts, because glucose transporters are ubiquitous.…”
Section: Discussionmentioning
confidence: 99%